2000
DOI: 10.1002/1097-0142(20000815)89:4<890::aid-cncr23>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Fatal liver failure after the administration of raltitrexed for cancer chemotherapy

Abstract: BACKGROUND Acute fatal liver failure is a relatively rare event after the administration of antineoplastic drugs. To the authors' knowledge, there have been no published reports of this phenomenon after the administration of the widely applied cytotoxic agent raltitrexed. METHODS The authors present two cases of fulminant fatal liver failure that occurred after the administration of raltitrexed as anticancer chemotherapy. RESULTS A female patient age 76 years and a male patient age 56 years were given raltitre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Nevertheless, grade 3 or 4 hepatotoxicity has been observed in 3% to 24% of adults with solid tumors after raltitrexed administration (3,24,22). Fulminant hepatic necrosis, an apparently rare and idiosyncratic adverse event, has also been reported in two adults after raltitrexed administration (25). Other grade 3 adverse events after raltitrexed included fatigue, diarrhea, and myelosuppression (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, grade 3 or 4 hepatotoxicity has been observed in 3% to 24% of adults with solid tumors after raltitrexed administration (3,24,22). Fulminant hepatic necrosis, an apparently rare and idiosyncratic adverse event, has also been reported in two adults after raltitrexed administration (25). Other grade 3 adverse events after raltitrexed included fatigue, diarrhea, and myelosuppression (3).…”
Section: Discussionmentioning
confidence: 99%
“…He noted that these elevations were reversible, returning to baseline in subsequent courses without dose reduction and were not associated with significant liver pathology. However, raltitrexed was associated with significant liver toxicity in other studies, including death from fulminant hepatic necrosis (25,26). Liver toxicity correlated with elevated baseline transaminases and high cumulative raltitrexed dose in these studies (26).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying 5FU resistance has been investigated with a focus on the level of the thymidylate synthase (TS) ternary complex formed with fluorodeoxyuridine monophosphate (FdUMP) [11][12][13] . Raltitrexed is a specific TS inhibitor that does not require modulation effects on RNA [14][15][16] . A meta-analysis that included 11 studies with 4622 colorectal cancer (CRC) patients reported equivalent OS and overall response rates (ORRs) with acceptable toxicities between traditional 5FU-and raltitrexed-based regimens [16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Raltitrexed is a speci c TS inhibitor which doesn't requires modulation effects on RNA [13,14,15]. A meta-analysis included 11 studies with 4622 CRC patients leads to an equivalent overall survival and response rates with acceptable toxicities comparing with traditional 5-uorouracil-based regimen and raltitrexed-based regimen [16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%